2011
DOI: 10.3174/ajnr.a2490
|View full text |Cite
|
Sign up to set email alerts
|

Size and Shape of the Corpus Callosum in Adult Niemann-Pick Type C Reflects State and Trait Illness Variables

Abstract: BACKGROUND AND PURPOSE:Variable alterations to the structure of the corpus callosum have been described in adults with NPC, a neurometabolic disorder known to result in both white and gray matter pathology. This study sought to examine the structure of the callosum in a group of adult patients with NPC and compared callosal structure with a group of matched controls, and to relate callosal structure with state and trait illness variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
4
35
0
Order By: Relevance
“…44 As described, these regions are in areas where there is significant overlap between regional toxic ganglioside excess and NFT accumulation. It is also possible that given the widespread white matter changes in NPC, 4,5 volumetric loss in these regions is reflective of pathology in their attenuated anatomic interconnections. If these hub regions are preferentially affected, then this potential suggests that select neocortical regions that are similarly attenuated, such as entorhinal and retrosplenial cortices and frontal regions such as orbitofrontal and dorsolateral prefrontal zones, [44][45][46] may also show regional vulnerability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 As described, these regions are in areas where there is significant overlap between regional toxic ganglioside excess and NFT accumulation. It is also possible that given the widespread white matter changes in NPC, 4,5 volumetric loss in these regions is reflective of pathology in their attenuated anatomic interconnections. If these hub regions are preferentially affected, then this potential suggests that select neocortical regions that are similarly attenuated, such as entorhinal and retrosplenial cortices and frontal regions such as orbitofrontal and dorsolateral prefrontal zones, [44][45][46] may also show regional vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Because of the rarity of adult patients, few studies have examined brain changes in the disease at a group level and their relationship with clinical variables. 4,5 We previously used VBM to demonstrate that gray matter changes in NPC were most significant in basal and subcortical regions, with reductions in volume in the hippocampus, thalamus, cerebellum, and striatum. 5 These findings matched both animal and human models of NPC, where these regions show the greatest ganglioside accumulation, 6 and where humans develop NFTs.…”
mentioning
confidence: 99%
“…We have also found significant reductions in callosal thickness, and significant correlations have been found between callosal thickness and illness duration and severity. That investigation also found significant correlations between callosal thickness and eye movement characteristics such as horizontal saccadic gain and peak velocity, and self-paced saccade count [20]. Specific investigation of subcortical grey matter structures have also found significant reductions in thalamus, striatum, and hippocampus in NPC patients, and reductions to the left hippocampus were significantly correlated with Iturriaga score and with measures of cognition [21].…”
Section: Discussionmentioning
confidence: 77%
“…The reasons for these apparently contradictory findings are unclear. It is possible that the non-progression of clinical ataxia as measured by the BARS in the patient group, in spite of cerebellar volume loss, could reflect an effect of treatment on other brain regions known to be affected in NPC, such as neurons in the basal ganglia [7,21], brainstem and vestibular system [22,25], or connecting white matter tracts [7,20]. The Iturriaga scale is a composite of a number of different motor deficits (manipulation, ambulation, language, and swallowing), and thus is presumed to reflect a broader range of motor circuits within the wider brain, and thus may capture a broader range of treatment effects in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral widespread reductions were found in most major white-matter tracts in the patient groups, including in both projection and association fibres. The thickness and shape of the corpus callosum are also found to be significantly reduced in NPC patients compared to control groups, and the degree of these changes correlated with illness measures in both adult (Walterfang et al 2011) and paediatric (Lee et al 2014) patients. One of the few longitudinal studies of NPC disease progression in treated and untreated patients found that cerebellar white matter was lost at a significantly faster rate in untreated patients than in patients treated with miglustat (Bowman et al 2015).…”
Section: Discussionmentioning
confidence: 87%